1997
DOI: 10.1038/nm0597-571
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bladder-urethral sphincter dysfunction in mice with targeted disruption of neuronal nitric oxide synthase models idiopathic voiding disorders in humans

Abstract: Idiopathic voiding disorders affect up to 10-15% of men and women. We describe bladder abnormalities in mice with targeted deletion of the gene for neuronal nitric oxide synthase which model the clinical disorders. The mice possess hypertrophic dilated bladders and dysfunctional urinary outlets which do not relax in response to electrical field stimulation or L-arginine. The mice also display increased urinary frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 15 publications
9
89
0
2
Order By: Relevance
“…Although nNOS was shown to be the major NOS isoform in the lower urinary tract (5), its gene invalidation did not affect bladder strip contractility or relaxation after chemical and electrical stimulations (28), suggesting that the reported effects on urodynamics and micturition were secondary to alterations of urethral resistances (5,18,28). We therefore focused on the dynamic control of urethral resistances by E 2 through the nNOS pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although nNOS was shown to be the major NOS isoform in the lower urinary tract (5), its gene invalidation did not affect bladder strip contractility or relaxation after chemical and electrical stimulations (28), suggesting that the reported effects on urodynamics and micturition were secondary to alterations of urethral resistances (5,18,28). We therefore focused on the dynamic control of urethral resistances by E 2 through the nNOS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Increased bladder weight and maximal bladder pressure at leakage suggested that nNOS disruption resulted in increased uretral resistances, which did not however translate into measurable alterations of the voiding patterns (28). In male animals, however, targeted disruption of the nNOS gene resulted in dysfunctional bladder outlet (5). Interestingly, eNOS immunoreactivity was observed in endothelium of submucosa blood vessels and in urothelium of the urethra, whereas nNOS expression was restricted to nerve fibers throughout the inner lamina propria and muscular layer, thereby supporting an exclusive control of urethral muscle relaxation by nNOS (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These mice displayed increased frequency of micturition. 20 In another study, blockade of the NO pathway influenced the function of the lower urinary tract, as studied by cystometry in conscious rats and in vitro, in isolated muscle strips from the rat detrusor and urethra. 21 The theory that NO has a role in the development of LUTS is further supported by the characterization and functional relevance of PDE isoenzymes in the human prostate, urethra and bladder wall.…”
Section: Luts and Ed: Pathophysiological Correlationsmentioning
confidence: 99%